INFLUENCE OFTHIRD PARTY FUNDS (TPF), MUDHARABAH, AND MUSYARAKAH FINANCING ON PROFITABILITY AT BANK MUAMALAT INDONESIA FOR THE PERIOD 2019–2024 - Chetty Tristantia Tarigan; Muttaqien Muttaqien; Rico Nur Ilham; Ristati Ristati (PT. Intelek Cendikiawan Nusantara, 2025)
This study investigates the effect of Third-Party Funds (TPF), Mudharabah financing, and Musyarakah financing on the profitability of Bank Muamalat Indonesia during the 2019–2024 period. The research employs a quantitative approach using secondary data obtained from the annual financial reports of Bank Muamalat Indonesia. Multiple linear regression analysis was applied to test the relationship between independent variables (TPF, Mudharabah, and Musyarakah) and the dependent variable (profitability measured by Return on Equity/ROE). The findings reveal that TPF has no significant effect on profitability, indicating that the accumulation of third-party funds does not necessarily improve financial performance due to potential inefficiencies in fund management or high cost of funds. In contrast, Mudharabah financing shows a positive and significant effect on profitability, suggesting that profit-sharing investment schemes contribute effectively to income generation. Similarly, Musyarakah financing also has a positive and significant impact on profitability, emphasizing the role of partnership-based financing in enhancing returns. The study concludes that while third-party funds play an essential role in banking operations, their contribution to profitability depends on efficient utilization, whereas profit-sharing financing such as Mudharabah and Musyarakah directly strengthens financial performance.